Prevalence evaluation of apical periodontitis and its relationship with endodontic and restorative treatment in a community in Southern Brazil - Saporiti, Julia Machado; Gomes, Andressa; Damian, Melissa Feres; Ferreira, Nadia de Souza (Brazilian Dental Science, 2020)
Objective: The aim of this study was evaluate radiographically prevalence of apical periodontitis (AP) in endodontically treated teeth (ETT) and relate with demographic factors, quality of endodontic treatment and coronal restoration. Material and methods: Data were collected from dental records wich contained full-mouth radiographic series. In ETT, arch, dental group and presence of AP were evaluated. Quality of root canal filling, presence and quality of coronal restoration and type of restorative material were also collected. Data were evaluated using descriptive statistics and Chi-square Test. Results: Of 70 patients included in the final sample, the majority were female (54.3%) and age ranged from 13 to 77 years (47.14 ± 13.18). Of 1,333 teeth evaluated, 73 (5.4%) had endodontic treatment, being the majority maxillary (74%) and anterior teeth (52.1%). Of teeth without endodontic treatment, 320 (25.4%) had AP. Failure rate was high (52.8%) and quality of root canal filling and coronal restoration were considered inadequate in majority cases (58.3% and 47.7%, respectively). Dental group had a statistically significant relationship with presence of AP in ETT, being more frequent in anterior teeth (p = 0.019). Conclusion: It was concluded that prevalence of AP in ETT was high and dental group was the factor that most influenced prevalence of AP in ETT. Keywords Apical periodontitis; Radiography; Root canal filling.